The Influence of Dictation Strategy in Improving Listening Skill of Senior High School Students - Saragih, Dhea; Marpaung, Anissa; Purba, Dame Setia Lamtiur; Leonardo, Pebri; Napitupulu, Selviana (Jurnal Pendidikan Indonesia, 2022)
Background : The implementation of this research was motivated by the results of researchers’ observations on students who still had many difficulties in listening. Students still have difficulties to listen in English due to the position of Indonesian students as foreign learners. Objective : The objective of this research is to know the influence of dictation strategy in teaching listening for Senior High School students and to find out the advantages of dictation strategy in teaching listening. Methods : The research method used in this research is survey method. The population of this research was the students of SMA Swasta Assisi. Therefore, the sample was the XI Social 1 students of SMA Swasta Assisi. Results : The results of this research were described through surveys distributed by researchers to students. The survey was filled by students based on their perceptions of dictation. The results of this research stated that dictation could affect the ability to hear students. Conslusion : Based on the research conducted by the researchers, we conclude that dictation was truly affected students’ listening skills based on their perceptions and experiences.